Pengaruh Kebijakan Moneter dan Fiskal terhadap Pengangguran di Indonesia - Triyas Ayu Hadi Setiowati; Ris Yuwono Yudo Nugroho (Universitas Pembangunan Nasional Veteran Jawa Timur, 2021)
The purpose of this study is to analyze the impact of monetary policy as seen from the BI Rate and the money supply (M2, and fiscal policy as seen from government spending and tax revenue in influencing the unemployment rate in Indonesia. The approach used in this research is quantitative. The data used are the BI Rate, the money supply (M2), government spending, tax revenue and unemployment in the form of time series data in an annual form from 1995 to 2019. The method used in this study is the Vector Auto analysis model. Regression (VAR). The stages used in this research test are a stationarity test, optimum lag test, VAR stability test, impulse response test, and variance decomposition test. The results of the impulse response indicate that the unemployment variable responds most to the shock of the interest rate variable (monetary policy) compared to other variables. The results of variance decomposition indicate that the contribution given by the BI Rate to the unemployment rate is the most significant relative to the contribution given by the variable money supply (M2), government spending, and tax revenue